Nucleated red blood cells as predictors of mortality in patients with acute respiratory distress syndrome (ARDS): an observational study - Mario Menk; Lena Giebelhäuser; Gerald Vorderwülbecke; Martina Gassner; Jan A. Graw; Björn Weiss; Mathias Zimmermann; Klaus-D. Wernecke; Steffen Weber-Carstens (Annals of Intensive Care, 2018)
Abstract Background Nucleated red blood cells (NRBCs) in critically ill patients are associated with increased mortality and poor outcome. The aim of the present study was to evaluate the predictive value of NRBCs in patients with acute respiratory distress syndrome (ARDS). Methods This observational study was conducted at an ARDS referral center and included patients from 2007 to 2014. Daily NRBC counts were assessed and the predictive validity of NRBCs on mortality was statistically evaluated. A cutoff for prediction of mortality based on NRBCs was evaluated using ROC analysis and specified according to Youden’s method. Multivariate nonparametric analysis for longitudinal data was applied to prove for differences between groups over the whole time course. Independent predictors of mortality were identified with multiple logistic and Cox’ regression analyses. Kaplan–Meier estimations visualized the survival; the corresponding curves were tested for differences with the log-rank test. Results A total of 404 critically ill ARDS patients were analyzed. NRBCs were found in 75.5% of the patients, which was associated with longer length of ICU stay [22 (11; 39) vs. 14 (7; 26) days; p < 0.05] and higher mortality rates (50.8 vs. 27.3%; p < 0.001). Logistic regression analysis with mortality as response showed NRBC positivity per se to be an independent risk factor for mortality in ARDS with a doubled risk for ICU death (OR 2.03; 95% CI 1.16–3.55; p < 0.05). Also, NRBC value at ICU admission was found to be an independent risk factor for mortality (OR 3.25; 95% CI 1.09–9.73, p = 0.035). A cutoff level of 220 NRBC/µl was associated with a more than tripled risk of ICU death (OR 3.2; 95% CI 1.93–5.35; p < 0.0001). ARDS patients below this threshold level had a significant survival advantage (median survival 85 days vs. 29 days; log rank p < 0.001). Presence of a severe ARDS was identified as independent risk factor for the occurrence of NRBCs > 220/µl (OR 1.81; 95% CI 1.1–2.97; p < 0.05). Conclusions NRBCs may predict mortality in ARDS with high prognostic power. The presence of NRBCs in the blood might be regarded as a marker of disease severity indicating a higher risk of ICU death.